THE DEVELOPMENT OF MATHEMATICS TEACHING MEDIA ‘OPUNG HANS’ BASED ON IAI - Mailani, Elvi; Simanihuruk, Akden; Manurung, Imelda Free Unita (Journal of Community Research and Service, 2019)
The aim of this research is to develop a media for learning mathematics in "Opung HAN" elementary school based on Interactive Audio Instruction (IAI) for students majoring in UNIMED elementary school teacher education. The IAI-based "Opung HAN" fraction media was compiled based on observations during the learning and analysis conducted on the dictates of high-class mathematics education courses and interviews conducted with elementary school teacher education students, where teachers were very difficult to convey material related to fractions, The teacher does not know what media to use in teaching broken material. On the other hand, in the high school mathematics education textbook, there is also no media / teaching aids that can be used to teach fractional material. The specific purpose of this research is: developing IAI-based "Opung HAN" fraction media which will later be used by students majoring in primary school teacher education in teaching fraction material when they later become a teacher. This research uses development research (Developmental Research). The subjects of this study were students majoring in primary school teacher education at the State University of Medan. In the initial stage, observations were made during the learning process, analysis of the dictates of high-level mathematics education courses and continued with interviews with students. From the results of these observations and interviews, an initial draft of the IAI-based "Opung HAN" fraction was compiled. Furthermore, the initial design of the IAI-based "Opung HAN" fraction media was validated by a team that aimed to assess the quality of these elementary mathematics learning media fractions so that the fractional media became effective learning media which would later be used by lecturers and students in the lecture process.Keywords :  IAI, Fraction media, math learning.